Condições de trabalho docente nas escolas de educação básica no Brasil: uma análise quantitativa - Edmilson Antonio Pereira Junior (2017)
This thesis investigated the conditions of teachers work in basic education units, identifying dimensions found in comprehensive databases, verifying the set of relationships between them and assessing their effects on teacher retention, medical leaveand professional satisfaction, analyzed as finalistic results. In the literature, the teachers work conditions constitute the support for the appropriated development of teaching activities in schools. It has the capability to attract new professionals and can hol teachers in educational establishments. This study adopted a quantitative methodology, the primary sources being the School Census, the Prova Brasil (Brazil Exam), both developed by the National Institute of Educational Studies and Researches Anísio Teixeira (Inep/MEC), and the research Teacher Work in Basic Education in Brazil (Gestrado/UFMG), carried out by sampling, in seven Brazilian states (Minas Gerais, Pará,Paraná, Goiás, Espírito Santo, Rio Grande do Norte and Santa Catarina). In this work was developed a bibliographic search of the national academic production on the teachers work conditions, which resulted in 95 studies within the scope of this thesis. These productions were explored in order to define the concept of "teachers work conditions inbasic education units" and the analytical model adopted. Analytically, it was verified the existence or not of differences in the measures due to characteristics of the schools (administrative dependency, stage of basic education, size and location of the school). Using survey data analysis, the statistical technique of Analysis of Variance was established to perform the comparison between the averages of the subgroups formed,inferring the existence or not of differences between them. Subsequently, it was implemented a simultaneous analysis of multiple measures of teachers work conditions in schools, of the school context and the factors resulting from these conditions. The statistical technique of Structural Equations Modeling was employed, allowing estimating measures on the intensity and the significance of the relationships between the variables and attesting the reliability and validity of the models. Two analytical models were structured. The first one included the constructs of school policing and school surveillance, as well as the scale of school infrastructure, seen as dimensions of working conditions in schools; the indicator of socioeconomic level of the schools, considered a context variable; and the retention rate of teachers, which is understood as a contingency element of working conditions. The second one presented as dimensions of teachers work conditions in the schools the indicators of the degree of control of activities; frequency of development of activities with co-workers; perception of classroom conditions; and perception of the conditions of the educational unit; and presented as contingency elements the professional satisfaction and the medical leave rate. The models attested the influence of teachers work conditions in schools in the finalistic results analyzed in this thesis.